An Investigation of Auroral E Region Energy Exchange Using Poker Flat Incoherent Scatter Radar Observations During Fall Equinox Conditions. Issue 10 (21st October 2021) - Zhan, Weijia; Kaeppler, Stephen R.; Larsen, Miguel F.; Reimer, Ashton; Varney, Roger
Abstract: We present new results using data collected by the Poker Flat Incoherent Scatter Radar (PFISR) of energy transfer rates, which include the effects from neutral winds in the high latitude E‐region ionosphere‐thermosphere (IT) during Fall 2015. The purpose of our investigation is to understand the magnetic local time (MLT) dependence of the peak energy transfer, which occurs asymmetrically in the morning‐evening (dawn‐dusk) MLT sector. The statistical characteristics of both altitude‐resolved and altitude‐integrated energy transfer rates in the auroral E region local to PFISR during different geomagnetic conditions are quantified. Our analysis shows that the geomagnetic activity level has large impacts on the energy transfer rates. In contrast with previous investigations, we find both the altitude integrated electromagnetic (EM) energy transfer rate and Joule heating rate are larger in the evening sector than in the morning sector during all geomagnetic activity conditions. We also observe a non‐negligible negative EM energy transfer rates below 110 km in the morning sector during active conditions, which is associated with neutral winds during this MLT interval. The statistical results show that the neutral winds tend to increase the Joule heating rate in a narrow altitude range in the morning sector and impact a broader region with respect to altitude and time in the evening sector in the E region under moderate and active conditions. We find that during quiet conditions that the neutral winds have a significant contribution to the Joule heating and contribute up to 75% of the Joule heating. However, during active conditions the enhanced electric fields are a dominant driver of Joule heating, while the neutral wind effects can reduce the Joule heating rates by 25% or more relative to the passive heating rates. Key Points: Energy transfer rates are estimated from Poker Flat Incoherent Scatter Radar (PFISR) measurements for the first time The electromagnetic energy transfer rate and the Joule heating rate are larger in the evening sector versus the morning sector Negative electromagnetic energy transfer rates occur below 110 km in the morning sector during disturbed geomagnetic conditions